2014
DOI: 10.1007/s13524-013-0277-2
|View full text |Cite
|
Sign up to set email alerts
|

The Death of Marriage? The Effects of New Forms of Legal Recognition on Marriage Rates in the United States

Abstract: Some conservative groups argue that allowing same-sex couples to marry reduces the value of marriage to opposite-sex couples. This article examines how changes in U.S. legal recognition laws occurring between 1995 and 2010 designed to include same-sex couples have altered marriage rates in the United States. Using a difference-in-differences strategy that compares how marriage rates change after legal recognition in U.S. states that alter legal recognition versus states that do not, I find no evidence that all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
2
23
0
Order By: Relevance
“…7 These findings show that DOMA policy was associated with lower relationship stability for cohabiting couples, which is consistent with prior work that established the importance of context in assessments of stability (Joyner et al 2014). Yet, DOMA policy is not associated with relationship stability for married couples, which is consistent with aggregate-level analyses showing no association between DOMA policies and different-sex marriage and divorce (Dillender 2014; Langbein and Yost 2009). The DOMA legislation indicator may be a proxy for other contextual variables that are associated with stability.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…7 These findings show that DOMA policy was associated with lower relationship stability for cohabiting couples, which is consistent with prior work that established the importance of context in assessments of stability (Joyner et al 2014). Yet, DOMA policy is not associated with relationship stability for married couples, which is consistent with aggregate-level analyses showing no association between DOMA policies and different-sex marriage and divorce (Dillender 2014; Langbein and Yost 2009). The DOMA legislation indicator may be a proxy for other contextual variables that are associated with stability.…”
Section: Discussionsupporting
confidence: 77%
“…The absence of a DOMA in a state did not mean that the state was supportive of marriage to same-sex couples, but rather that the state was not actively against marriages to same-sex couples. Although these policies are not associated with the formation or stability of marriages to different-sex couples at the aggregate level (Dillender 2014; Langbein and Yost 2009), no study has assessed this policy indicator and the stability of same-sex or different-sex cohabiting couples. We introduce policy environment for same-sex couple relationships by including an indicator measuring whether the state of residence is one in which DOMA has been enacted by a constitutional amendment that defines marriage as the union of a woman and a man.…”
Section: Introductionmentioning
confidence: 99%
“…Our article adds to a small but growing literature on marriage-like contracts for same-sex couples afforded by the recent expansion of such rights (Burn and Jackson 2014;Carpenter and Gates 2008;Dillender 2014Dillender , 2015Langbein and Yost 2009;Trandafir 2015). Exploiting cross-sectional and time variation, a number of studies have found no evidence of the legalization of same-sex unions eroding traditional values as measured by marriage, divorce, or abortion rates.…”
Section: Introductionmentioning
confidence: 86%
“…In that period, State-sanctioned persecution of Jews, lepers, male homosexuals, and heretics emerged to form what Moore (2007) coined "the prosecuting society." 4 For the United States, see Langbein andYost (2009) andDillender (2014). For the OECD, see Trandafir (2015).…”
Section: Introductionmentioning
confidence: 99%
“…A potential issue with including any variable to distinguish between married and unmarried opposite‐sex couples is that the laws may alter which category a couple fits into if the extensions in legal recognition affect marriage decisions for people in that state. In Dillender (), I find that extending marriage to same‐sex couples in the United States has had no effect on opposite‐sex marriage rates, but I do find that extending non‐marriage legal recognition to opposite‐sex couples results in a decline in the opposite‐sex marriage rate, likely because a portion of people who would have gotten married opt for non‐marriage legal recognition instead. When considering how legal recognition laws affect the stocks of marriage, I find little or no effect of any type of legal recognition laws, suggesting the pools of married couples are slow to change in any significant ways because there is already a high stock of married people…”
Section: Data and The Empirical Strategymentioning
confidence: 98%